Case report: Exploring autosomal recessive woolly hair: genetic and scanning electron microscopic perspectives on a Japanese patient - Minakawa, Satoko; Matsuzaki, Yasushi; Higashino, Toshihide; Suzuki, Tamio; Tomita, Hirofumi; Akasaka, Eijiro; Sawamura, Daisuke (Frontiers in Medicine, 2024)
Woolly hair (WH) is a hair shaft anomaly characterized by tightly curled hair that typically stops growing at a few inches. Autosomal recessive WH (ARWH; OMIM no. 278150/604379/616760) has been reported to be caused by variants in genes coding lysophosphatidic acid receptor 6 (LPAR6), lipase H (LIPH), or keratin 25 (KRT25). In this study, we conducted a scanning electron microscopic (SEM) examination of the hair of a 3-year-old Japanese ARWH patient. The SEM revealed that her affected hair had an irregular and rough cuticle compared to her mother’s hair. Many irregular small projections and longitudinal grooves were seen on the surface of the patient’s hair shaft, and some free margins of the hair cortex were raised or serrated. Her hairs were oval-shaped on the cross-section. Mutation analysis revealed a homozygous pathogenic variant (c.736 T > A; Cys246Ser) in exon 6 in LIPH. In our clinic, we identified three additional cases with the homozygous Cys246Ser variant and one case with compound heterozygous variants in LIPH: Cys246Ser and c.671C > G (Pro224Arg). Consequently, genetic analyses, including genotype–phenotype correlation involving rare LIPH variants, have become more crucial in the Japanese population.